Análisis de costos del tratamiento farmacológico de pacientes adultos ambulatorios de un hospital militar del oriente peruano, 2020 - Terrones Bardales, Martin Alonso (2022)
Introduction: The consumption of drugs and related drugs in an institution that provides primary health care is decisive for programming the acquisition of drugs, so knowing the population served and the consumption differentiated by therapeutic groups is important. Objective: To analyze the costs of treating adult patients treated in an outpatient clinic in a military hospital in eastern Peru, in 2020. Methodology: This was an analytical, non-experimental, retrospective longitudinal study. The study population corresponded to active military personnel (officers and non-commissioned officers), all were included in the study. Results: The population served (152 patients) was mainly noncommissioned officers 123 (86%) against the population of officers served 20 (14%). The vast majority of patients requested more than one care during the year 2020, and consequently had one diagnosis per consultation, but some patients had more than one per consultation; which derived according to the international classification of diseases - 10 (ICD-10) in a total of 128 causes of morbidity, with a total of 1020 assigned diagnoses whose frequency due to morbidity was very varied. Conclusions: The military population attended by consultation external was predominantly male non-commissioned officers of the adult - adult category, the costs by type of medication determined that the highest expense corresponded to antibiotics, gastro-intestinal drugs, NSAIDs, drugs for the respiratory system, antiparasitics; followed by other therapeutic groups whose acquisition required less expense.